A Case of Primary Myelofibrosis With Transformation to Leukemia Cutis. (January 2022) - Saleh, Jasmine; Regmi, Aayushma; Speiser, Jodi J.; Mudaliar, Kumaran M.; Omman, Reeba; Velankar, Milind; Mirza, Kamran M.
Abstract : Abstract: We report an extraordinary case of primary myelofibrosis with transformation to leukemia cutis. A 64-year-old Caucasian man with a history of JAK2-positive primary myelofibrosis presented with erythematous papulonodules on his right lower extremity. A punch biopsy revealed a normal epidermis with an underlying diffuse dermal infiltrate composed of medium-to-large-sized myeloid cells and leukocytes. Neoplastic cells were immunoreactive for LCA, CD34, CD61, CD117, and CD68 and negative for lysozyme, CD20, CD3, myeloperoxidase, and TdT. These findings were consistent with a diagnosis of leukemia cutis. A concurrent bone marrow biopsy demonstrated a markedly fibrotic, hypercellular marrow without a significant increase in blasts. With no morphologic evidence of bone marrow involvement by acute myeloid leukemia, our case suggests that the patient's primary myelofibrosis transformed to leukemia cutis. Our patient died 2 months after the onset of his skin nodules. Our case demonstrates that leukemia cutis should be included in the differential diagnosis for cutaneous nodular lesions in patients with a history of an advanced-stage hematological malignancy.